Rare Pancreatic Anomaly: Annular Pancreas - Mehmet Kapan; Etibar Mammadov; Mehmet Suat Yalçın; Murat Başaran; Burak Özşeker (Diagnostic and Interventional Endoscopy)
Acute pancreatitis is defined as inflammation of the pancreas gland accompanied by abdominal pain and elevated levels of amylase and lipase. The reported annual incidence of acute pancreatitis varies between 4.9 and 35 per 100 000 people. Annular pancreas is a rare cause of acute pancreatitis. The incidence of annular pancreas varies between 5 and 15 per 100 000. It presents with different clinical symptoms and can cause nausea, vomiting, cholangitis, and pancreatitis. In this case report, we present one case showing that the etiology of acute pancreatitis is annular pancreas.